A Study of Synergy of Combination of Eosin B with Chloroquine, Artemisinin, and Sulphadoxine-Pyrimethamine on Plasmodium falciparum In Vitro and Plasmodium berghei In Vivo - Sedigheh Sadeghi; Zarrintaj Valadkhani; Alireza Sadeghi Tafreshi; Mohammad Arjmand; Hossein Nahravanian; Farideh Vahabi; Neda Soori; Maryam Mohammadi; Masoomeh Meigooni; Zahra Zamani (Journal of Tropical Medicine)
Background and Objectives. Artemisinin is the popular antimalarial medication, but it has to be used in combination with other drugs as its monotherapy causes resistance. The effectiveness of eosin B, a laboratory stain, as a competent antimalarial agent was identified earlier. It was tested in combination with different antimalarial drugs such as artesunate (a derivative of artemisinin) or chloroquine or sulphadoxine-pyrimethamine in vitro on Plasmodium falciparum and in vivo on Plasmodium berghei using Peter’s suppression test. Methods. Drug assessment was carried out singly or in combination on Plasmodium falciparum in vitro using the candle jar method at three inhibitory concentrations. Percent parasitemia of live cells was obtained by microscopic counting. Peter’s suppression test was carried out on mice infected with Plasmodium berghei after 3 administration of the drugs singly and in combination, and parasites were counted by microscopy for 10 days. Results. Synergy was exhibited by isobolograms of eosin B combined with artesunate and sulphadoxine-pyrimethamine with more than 10 fold reduction of all drugs in vitro. A good combination index was obtained with artesunate at 50% inibitory concentration with 3.4 nM eosin B and 1.7 nM artesunate in contrast to 124 nM eosin B and 7.6 nM artesunate singly. In vivo studies also showed a considerable lowering of the effective dose of eosin B 30 mg/kg: artesunate 3 mg/kg with 200 mg/kg eosin B and 60 mg/kg artesunate separately. Sulphadoxine-pyrimethamine seemed to have the greatest synergistic effect with a combination index of 0.007, but this could be due to it consisting of a combination of three drugs. Eosin B’s combination index with chloroquine was fair, and in vivo tests too did not show as much competence as the other two drugs. Conclusion and Interpretation. It can be concluded that eosin B can be used in combination with antimalarial drugs with favorable results.